Social Partners and Gender Equality
XXIV, 315 p. 4 illus., 3 illus. in color.
Keywords: “This book offers a collection of insightful and important studies of a long neglected area in gender and politics research. It spans from case studies of gender equality in national trade unions in Europe to the role of social partners in the European Union. A must-read for everyone who wants to understand more about the recent development of gender, power and corporatism in Europe.” – Christina Bergqvist, Professor of Political Science, Uppsala University, Sweden “This volume will interest politics researchers/students as well as those in other fields including sociology, employment relations, business and management studies. Its focus on gender and social partners and how they both shape and challenge gender inequalities is more than timely, it is absolutely essential for understanding how a better world can be built post-pandemic. Individually the chapters address a wide range of pressing issues situated in context of European countries which the editors pull together analytically and theoretically in their overview chapter. Highly recommended reading.” – Gill Kirton, Professor of Employment Relations, Queen Mary University of London, UK This book breaks new ground in gender and politics research by studying the multiple ways in which gender and intersectional equalities shape and are shaped by social partners representing employers and employees in Europe. The chapters in this volume explore the impact of social partners on (in)equalities, taking into account phenomena such as neoliberalisation, austerity, and the COVID-19 crisis. Thisvolume contributes to research on issues such as domestic work, the gender pay gap, and the persistent undervaluation of women’s labour and feminized reproductive labour, in particular care work. It also represents a significant contribution to the literature on gender equality policy. The book’s focus on social partners provides important insights that help to explain the persistence of gender inequalities and the difficulties of adopting and implementing policies to combat them. Anna Elomäki is Senior Researcher at Tampere University, Finland. Johanna Kantola is Professor of Gender Studies at Tampere University, Finland. Paula Koskinen Sandberg is Postdoctoral Researcher at Tampere University, Finland.